The use of framework analysis in the alignment of the laws of rugby to skeletal development of children and adolescents - Sinnett, Faye Victoria (My University, 2019)
Rugby, as a contact sport, has inherent risks of injury. Children and adolescents playing rugby at schoolboy level have a developing skeletal system and therefore injuries through this age of play may result in injuries to under-developed bones. This research study looked to identify whether the laws of rugby align to protect skeletal development of children and adolescents through law adaptations. Framework Analysis was used to develop a matrix which aligned the adapted laws of rugby with bone fusion ages. In future studies this can be used as a base for other areas of development and other sports. This matrix was further analysed to determine a severity rating scale and this scale identified some bones of the skull (occipital, sphenoid and zygomatic), upper limb (scapular, glenoid and clavicle) and lower limb (sacrum and pelvic girdle) as having a higher risk for severe injury. While these bones are at severe potential risk of injury it is important to note that only one measure of maturation was used and in future additional measures of maturation should be used. In conclusion, while the adapted laws of rugby do protect some bones of the developing skeletal system, they do not protect all of the developing bones of the skeletal system. The matrix could be used to guide future law makers in their endeavour of making the game of rugby safer for children and adolescents
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Occupational Therapy Johannesburg, 2019
Keywords: Rugby football--Social aspects; Radiography; Child development